EKONOMI POLITIK MEDIA: PADA PEMBERITAAN MENJELANG PEMILIHAN GUBERNUR BANTEN 2017 OLEH RADAR BANTEN DAN BARAYA TV - P, Achmad Nashrudin (Informasi, 2016)
Research on Political Economy of Media: At the news ahead of elections for the governor of Banten in 2017 by Radar Banten and Baraya TV, phenomenon triggered by the loosening of the values of objectivity and independence of the mass media in carrying out its functions as set in the Press Law and the Broadcasting Law. At the time of the campaign, the candidates for governor and lieutenant governor are competing to get the "place "˜and is known well as sell to prospective election promise to get sympathy. At the time, the media seemed to forget the function and position. This study aims to determine the phenomenon of media relations with the candidates and how the phenomenon of the political economy of media in both institutions (Radar Banten and Baraya Pos) at the time before the election for governor of Banten in 2017. This study uses this study used a qualitative approach, with the constructivist paradigm and using the method of data collection through the depth-interview, the informant was elected. The results of the study illustrate that media relations (relations between) media with prospective relatively loose, drawn from observations and interviews show that the two media are "very affectionate" with the candidates, and the media policy in lifting more headlines have suggested the economic interests vis a vis political interests.